Duchenne muscular dystrophy and dystrophin: pathogenesis and opportunities for treatment. - Nowak, K; Davies, K (2004)
Duchenne muscular dystrophy (DMD) is caused by mutations in the gene that encodes the 427-kDa cytoskeletal protein dystrophin. Increased knowledge of the function of dystrophin and its role in muscle has led to a greater understanding of the pathogenesis of DMD. This, together with advances in the genetic toolkit of the molecular biologist, are leading to many different approaches to treatment. Gene therapy can be achieved using plasmids or viruses, mutations can be corrected using chimaeraplasts and short DNA fragments, exon skipping of mutations can be induced using oligonucleotides and readthrough of nonsense mutations can be achieved using aminoglycoside antibiotics. Blocking the proteasome degradation pathway can stabilize any truncated dystrophin protein, and upregulation of other proteins can also prevent the dystrophic process. Muscle can be repopulated with myoblasts or stem cells. All, or a combination, of these approaches hold great promise for the treatment of this devastating disease.